Saberes tradicionais quilombolas e interface com agrobiodiversidade em Chapada dos Guimarães/MT - Brasil - Miranda, Rosenil Antônia de Oliveira (2021)
The practice of cultivating, managing and conserving agrobiodiversity in quilombola communities has contributed to several areas of scientific knowledge, due to its cultural and social importance in the face of genetic and cultural erosion today. The present study aimed to investigate and record the causal link between the action/tradition of traditional, ethnobotanical knowledge and the potential for ancestral agricultural conservation exercised in spaces modified by human intervention, called swiddens in the Cambambi (CC), Pingador (CP) communities. and Itambé (CI) located in the Municipality of Chapada dos Guimarães - Mato Grosso, Brazil. To record the ethnocategories of use of plant species cultivated and managed by the populations in the different landscape units, application of semi-structured and open interviews. Qualitative and quantitative data were collected from March 2019 to March 2020. For qualitative analysis, the landscape unit was divided into five categories: (a) cerrado; (b) kills; (c) farmland; (d) backyard and (e) vegetable garden. They were grouped into four ethnocategory of uses: Medicinal, Food, Ornamental and Condiments. In the quantitative approach, the Use Value of each species was calculated and to identify the plants with the greatest purpose, calculating the informing consensus through the Loyalty Level. As for naturalness, 94% say they are of African descent. 162 ethnovarieties of plant species were identified and distributed in 67 botanical families. The botanical families that had the highest number of species were Fabaceae, followed by Asteraceae, also occurring Lamiaceae, Solanaceae and Cucurbitaceae. It was found that the highest percentage of respondents were women, all over 18 years of age. As for the origin, 95% of the interviewees are from the city and state of Mato Grosso. For the level of education, most have elementary education. Creole seeds are obtained from gardens, gardens and backyards being Legumes (beans, soy and peas), Grasses (corn, sorghum, rye, rice, wheat, sugar cane), Musaceae (banana), Solanaceae (pepper, eggplant, jiló, tomato, smoke), Cucurbitaceae (pumpkin, watermelon), Caricaceae (papaya), Brassica (cabbage), Amaryllidaceae (onion, garlic, chives), Convolvulaceae (sweet potato), Fabaceae (peanut), Apiáceae (carrot, coriander), Euphorbiaceae (manioc), Anacardiaceae (mango, cashew), Myrtaceae (guava), Rutaceae (lemon, orange), Passifloraceae (passion fruit), Lauraceae (avocado), Malpighiaceae (acerola), Bromeliaceae (pineapple), Punic fruit (pineapple), Punic fruit (pineapple) pomegranate), Caryocaraceae (pequi). Species used for the food and medicinal categories and with multiple uses. Traditional rural communities have a large cultural heritage on the use and cultivation of food plants, especially through cultural practices based on in situ conservation in local landscape units. This practice reports broad representativeness, constituting itself as an important tool in the perpetuation of traditional knowledge among the quilombola population that still preserve information acquired from their ancestors.